2013
DOI: 10.1021/ja4086758
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Exchange and the Stoichiometry of Metal Chalcogenide Nanocrystals: Spectroscopic Observation of Facile Metal-Carboxylate Displacement and Binding

Abstract: We demonstrate that metal carboxylate complexes (L–M(O2CR)2, R = oleyl, tetradecyl, M = Cd, Pb) are readily displaced from carboxylate-terminated ME nanocrystals (ME = CdSe, CdS, PbSe, PbS) by various Lewis bases (L = tri-n-butylamine, tetrahydrofuran, tetradecanol, N,N-dimethyl-n-butylamine, tri-n-butylphosphine, N,N,N',N'-tetramethylbutylene-1,4-diamine, pyridine, N,N,N',N'-tetramethylethylene-1,2-diamine, n-octylamine). The relative displacement potency is measured by 1H NMR spectroscopy and depends most st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

91
1,368
5
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 779 publications
(1,469 citation statements)
references
References 143 publications
91
1,368
5
5
Order By: Relevance
“…Therefore, most of the previously reported results related to BiVO 4 ‐based photoanodes13, 14, 16, 19, 47, 51, 52, 53 were measured in sulfite oxidation condition to show photo‐electrochemical properties of BiVO 4 ‐based electrodes independently of its poor water oxidation kinetics, as shown in Table S2 (Supporting Information). The photo‐electrochemical current densities of the BiVO 4 ‐based photoanodes4, 13, 14, 16, 17, 19, 20, 21, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 64, 65, 66, 67, 68, 69, 77 were plotted as a function of potential versus RHE. Thus, we measured PEC properties of BiVO 4 ‐based anodes under sulfite oxidation to figure out the effect of ligand engineering.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, most of the previously reported results related to BiVO 4 ‐based photoanodes13, 14, 16, 19, 47, 51, 52, 53 were measured in sulfite oxidation condition to show photo‐electrochemical properties of BiVO 4 ‐based electrodes independently of its poor water oxidation kinetics, as shown in Table S2 (Supporting Information). The photo‐electrochemical current densities of the BiVO 4 ‐based photoanodes4, 13, 14, 16, 17, 19, 20, 21, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 64, 65, 66, 67, 68, 69, 77 were plotted as a function of potential versus RHE. Thus, we measured PEC properties of BiVO 4 ‐based anodes under sulfite oxidation to figure out the effect of ligand engineering.…”
Section: Resultsmentioning
confidence: 99%
“…The direct observation of the development and propagation of surface defects is enabled by the exceptionally thin NPs as the removal of just a few atoms from the (001) facets strains the lattice, inducing perforations. 8a While the aqueous solution of NH 4 OH, itself an L‐type (two‐electron donor) promoter ligand, enables the LE with thiostannate ligands to proceed rapidly, 9a it also supports degradation, likely following a process known as L‐promoted Z‐type ligand displacement. Calibrated HAADF STEM images showed that at least 50 % of the material was removed from the damaged areas (Figure S4 d, e).…”
mentioning
confidence: 99%
“…The displacement potency of a ligand depends on multiple attributes, such as electronic effects, chelation, and steric properties. 9a We varied the latter by replacing NH 4 OH with another promoter ligand pyridine, 3‐methylpyridine, or 2,6‐dimethylpyridine (DMP), which are all L‐type ligands, and found that all LE treatments resulted in perforation of the NPs; furthermore, treatment with DMP also resulted in material rearrangement from the NP core onto the surface (Figure S2). This structural damage always correlated with a dramatic decrease in PLQY (ca.…”
mentioning
confidence: 99%
“…They provide ''trap states'' for charge carriers, i.e., energy levels within the bandgap where the charge carrier is spatially localized. Indeed, the quantum efficiency of NC emission improves when the NC surface is covered with a protective shell of high-bandgap material [13,15,16,61,74,[243][244][245][246], or when ligands saturate chemical bonds on the surface [16,123,[247][248][249][250][251].…”
Section: Radiative Decay In Semiconductor Nanocrystals: Ns To Ls Timementioning
confidence: 99%
“…The simplest picture is that quenching can be suppressed by saturating chemical bonds of the surface atoms [15,16,61,[243][244][245][246][247][248][249]251]. This can be achieved by overcoating the NC either by a shell of another semiconductor or by a ligand layer.…”
Section: Radiative Decay In Semiconductor Nanocrystals: Ns To Ls Timementioning
confidence: 99%